M105. ACTIGRAPHIC MONITORING OF SLEEP-WAKE CYCLE IN SCHIZOPHRENIA OUTPATIENTS RECEIVING A LONG-ACTING INJECTABLE ANTIPSYCHOTIC: FEASIBILITY AND INITIAL RESULTS FROM A PROSPECTIVE RCT. (18th May 2020) - Yagoda, Sergey; Wolz, Robin; Weiden, Peter J; Claxton, Amy; Yao, Baiyun; Du, Yangchun
Abstract: Background: Patients with schizophrenia are known to experience many problems across the 24-hour sleep-wake cycle (SWC), including lower daytime physical activity levels, as well as a range of problems in nighttime sleep quality. However, self-report assessment of these parameters is challenging because of recall bias and confounding with other schizophrenia symptoms (eg, cognitive and negative symptoms). Quantitative measures such as sleep lab assessments are useful but may be prohibitively expensive and impractical for routine use, and do not represent sleep behavior in a real-world setting. Wearable digital measures such as actigraphy hold promise, but data on feasibility of longitudinal assessment of SWC are limited in schizophrenia outpatients. In this exploratory analysis, we evaluated feasibility and utility of wrist actigraphy to measure key activity and sleep parameters within a randomized, double-blind clinical trial. This trial followed recently stabilized schizophrenia outpatients on a fixed dose of a long-acting injectable (LAI) antipsychotic. Methods: Exploratory actigraphy assessments were carried out in a 25-week, prospective, randomized, controlled trial (RCT) primarily designed to evaluate safety and effectiveness of aripiprazole lauroxil (AL) for treatment of schizophrenia (1-day initiation regimen and a 2-month dose interval). Paliperidone palmitate (PP) was included as an active control. Patients were enrolled and randomized as inpatients during an acute exacerbation of schizophrenia, were discharged after 2 weeks, and were followed as outpatients for the remainder of the 25 weeks. Actigraphy was used to assess SWC during the outpatient part of the study, with patients being offered wrist-worn Axivity AX3 (Axivity Ltd) accelerometers for continuous wear on the nondominant hand in two 2-week sessions. The first session started at week 3 (cycle 1) and the second at week 9 (cycle 2). Upon return of the accelerometers to the study site, data were uploaded to a central data management system (TrialTracker™, IXICO plc) and were evaluated in 24-hour increments to exclude periods of non-wear; cycles were analyzed individually. Actigraphy parameters included total sleep time (TST; average total time asleep over 24 hours), sleep efficiency (proportion of time asleep when resting), activity (circadian rhythm MESOR; average activity level over 24 hours), and other common actigraphic variables. Results: The mean Positive and Negative Syndrome Scale (PANSS) total score in the population of patients remaining in the study at week 3 (n=162) was 75.7. Of these 162 patients, 145 received an actigraphy device and 126 provided ≥1 valid 24-hour recording interval in cycle 1 (n=113) and/or cycle 2 (n=81). Within-subject actigraphy profiles from cycle 1 and cycle 2 were consistent, allowing the analysis to be based on the combined data from the 2 cycles. For AL (n=61) and PP (n=65), values for mean±SD TST were 10.2±2.5 hours and 11.7±2.8 hours, sleep efficiency were 80.0%±9.4% and 82.8%±8.1%, and average activity (MESOR) were 122.0±33.5 counts/min and 104.0±36.0 counts/min, respectively. As baseline actigraphy was not collected prior to randomization in this study, conclusions regarding comparability between treatment groups are limited. Discussion: This exploratory analysis demonstrates that actigraphy monitoring is feasible in stabilized patients with schizophrenia in an outpatient setting. This dataset offers some evidence on the relative stability of SWC for individual patients over time, as well as possible group differences based on demographic, symptom, or treatment factors. Data from this analysis can provide guidance for future actigraphy studies in schizophrenia.